2009
DOI: 10.1002/path.2507
|View full text |Cite
|
Sign up to set email alerts
|

The development of multiple bladder tumour recurrences in relation to the FGFR3 mutation status of the primary tumour

Abstract: Non-muscle invasive bladder cancers (NMI-BCs) represent 75% of bladder cancers upon presentation. After removal of the primary tumour by transurethral resection, multiple recurrences continue to develop in 70% of patients. Consequently, prolonged and costly surveillance by cystoscopy is required. Mutations in the FGFR3 oncogene are common in NMI-BCs and are associated with a lower chance of progression to muscle-invasive disease. Here we analysed the consistency of FGFR3 mutations in primary and recurrent tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 32 publications
3
35
0
Order By: Relevance
“…Because this problem of urine sampling concerns all urinary tests that depend on the presence of tumor cells in the urine, this is an important issue and it would be of interest to determine the optimal time point and frequency of urine collection to improve the number of urinary tumor cells. Secondly, FGFR3 WT recurrences are sometimes found in patients with a primary FGFR3-mutant tumor (22). Whether this is the reason why some recurrences were missed here is not known at present because tumor material from the recurrences was not available for FGFR3 mutation analysis.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Because this problem of urine sampling concerns all urinary tests that depend on the presence of tumor cells in the urine, this is an important issue and it would be of interest to determine the optimal time point and frequency of urine collection to improve the number of urinary tumor cells. Secondly, FGFR3 WT recurrences are sometimes found in patients with a primary FGFR3-mutant tumor (22). Whether this is the reason why some recurrences were missed here is not known at present because tumor material from the recurrences was not available for FGFR3 mutation analysis.…”
Section: Discussionmentioning
confidence: 92%
“…Whether this is the reason why some recurrences were missed here is not known at present because tumor material from the recurrences was not available for FGFR3 mutation analysis. We have previously shown that the stage and grade of these recurrences do not differ from mutant recurrences (22). Therefore, the absence of a mutation cannot be correlated with progression to a more severe phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major problem in the management of patients presenting with NMIBC is that 70% will develop one or more recurrences and that recurrences can keep on developing for up to 25 years (9). Surveillance of these patients by cystoscopy is warranted (32).…”
Section: Discussionmentioning
confidence: 99%
“…Somatic mutations in the FGFR3 gene accompanied with losses of chromosome 9 are more frequent in NMIBC, whereas TP53 mutations are associated with muscle-invasive bladder cancer (MIBC) (4)(5)(6). Unfortunately, 70% of patients with NMIBC will have one or more recurrence after transurethral resection (TUR) and 10% to 20% of patients will eventually have progression to MIBC (7)(8)(9). Patients with NMIBC are currently stratified into low/intermediate and high-risk groups regarding progression and recurrence based on clinicopathologic parameters (10,11).…”
Section: Introductionmentioning
confidence: 99%